Work Force Management System Using Face Recognition - et. al., Nikhat Parveen, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
— The primary aim of this research is to build a web application for Work Force management using face-recognition to replace the traditional system being used to take attendance which is not very efficient. The traditional method being used is prone to errors and creates a lot of ambiguity in retrieving the data. With the help of technology, we are going to develop an automated system which can cut the problems in the traditional system. The technology that works behind is going to be the face recognition system. There is an admin module where the admin can register the individuals into the system. The system captures photos of the workers while registering. The face recognition engine is trained and then attendance can be detected. The attendance detected can be stored into the database and can be retrieved any point of time using the Django web server. This project can be used to manage the workforce in an easy way.